2017
DOI: 10.1016/j.ejim.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Transition of care: A set of pharmaceutical interventions improves hospital discharge prescriptions from an internal medicine ward

Abstract: An intervention group underwent significantly fewer medication changes in subsequent steps in the transition of care after a set of interventions performed during their hospital stay. Community pharmacists had to perform fewer interventions on discharge prescriptions. Altogether, this improves continuity of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…However studies from Australia and Switzerland show that GP appointments are often delayed. 4 , 5 In some countries, community pharmacists are therefore the first health care professionals encountered by the recently discharged patient, providing medication supply and pharmaceutical care. 2 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However studies from Australia and Switzerland show that GP appointments are often delayed. 4 , 5 In some countries, community pharmacists are therefore the first health care professionals encountered by the recently discharged patient, providing medication supply and pharmaceutical care. 2 …”
Section: Introductionmentioning
confidence: 99%
“…A recent intervention study in a Swiss region, aiming at optimising communication found a reduction of interventions by the community pharmacies after an in-hospital intervention. 4 But it is unknown if the performed optimisations met the pharmacists’ needs and objectives. To our knowledge, no study so far has compared the currently available information with the desired information in a mixed method study.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, healthcare professionals have developed and evaluated various interventions to detect and resolve potential DRPs at hospital discharge, thus avoiding adverse drug events (ADEs) [1,[6][7][8]. Medication reconciliation and medication reviews are two options to detect and resolve DRPs at transitions of care [9][10][11][12][13]. According to the World Health Organisation, different healthcare professionals are able to perform medication reconciliation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is affecting the range of professional groups in GIM, and healthcare more broadly, as they defend or adapt their professional boundaries and roles to these demands (Correia, 2013;Harvey, Thompson, Pearson, Willis, & Toffoli, 2017;Henderson, Willis, Toffoli, Hamilton, & Blackman, 2016;Newman & Lawler, 2009;Reeves, Nelson, & Zwarenstein, 2008;Shannon & French, 2005). For example, social workers, pharmacists, occupational therapists and physiotherapists in GIM units have experienced changes in their roles in the healthcare division of labour with greater emphasis on discharge-related responsibilities (Galati, Wong, Morra, & Wu, 2011;Goldman et al, 2016;Neeman et al, 2017). Physicians in these settings have pressures to prioritize their decision-making around patient flow with an increasing emphasis on the value of teaching residents about safe discharge (Greysen, Schiliro, Horwitz, Curry, & Bradley, 2012;Schoenborn & Christmas, 2013).…”
Section: Introductionmentioning
confidence: 99%